Cobalt: Canada's Forgotten Silver Boom Town - Baldwin, Douglas O. (Indigo Press, 2016)
Cobalt's rich history is full of the romance of prospecting, stories of immense wealth, deaths and mining accidents, struggles to obtain pure drinking water and fire protection, labour-management turmoil, legal conflicts between the town and the mining companies, the founding of the Ontario Provincial Police, and the struggles to provide religion, education, and leisure activities in a mining boom town. Its story is one of immense capital accumulation, labour strife, technological progress, new government policies and ventures, regional growth, and the struggle for law and order. The discovery of the fabulously rich silver mines led to the emergence of northeastern Ontario and helped Toronto to assert its financial dominance. –From Introduction
OCLC: 923568514
Keywords: Argent Mines et extraction Ontario Cobalt Histoire; Cobalt (Ont.) Histoire; Cobalt (Ont.) History; History; Ontario Cobalt; Silver mines and mining; Silver mines and mining Ontario Cobalt History

Women Challenging Unions: Feminism, Democracy, and Militancy - Briskin, Linda; McDermott, Patricia; Coulter, Rebecca; Baker, Patricia L.; Cuneo, Carl J.; Stinson, Jane; Richmond, Penni; White, Julie; Kumar, Pradeep; Fudge, Judy; Warskett, Rosemary; Messing, Karen; et al. (University of Toronto Press, 2016)
[This book] is a collection of original papers that presents a vision of an invigorated and vibrant labour movement, one that would actively seek the full participation of women and other traditionally excluded groups, and that would willingly incorporate a feminist agenda. This vision challenges union complicity in the gendered segmentation of the labour market; union support for traditionalist ideologies about women's work, breadwinners, and male-headed families; union resistance to broader-based bargaining; and the marginalization of women inside unions. All of the authors share a commitment to workplace militancy and a more democratic union movement, to women's resistance to the devaluation of their work, to their agency in the change-making process. The interconnected web of militancy, democracy, and feminism provides the grounds on which unions can address the challenges of equity and economic restructuring, and on which the re-visioning of the labour movement can take place. The first of the four sections includes case studies of union militancy that highlight the experiences of individual women in three areas of female-dominated work: nursing, banking, and retailing. The second and third sections focus on the two key arenas of struggle where unions and feminism meet: inside unions, where women activists and staff confront the sexism of unions, and in the labour market, where women challenge their employers and their own unions. The fourth section deconstructs the conceptual tools of the discipline of industrial relations and examines its contribution to the continued invisibility of gender. –Publisher's description
OCLC: 1011475719

Farm Workers in Western Canada: Injustices and Activism - Broadway, Michael J.; Bucklaschuk, Jill; Contractor, Delna; Dunlop, Darlene A.; Hambly, Brynna; Hamm, Zane; Kennett, Paul; Koshan, Jennifer; Lau, C. F. Andrew; Martinelli, J. Graham; McIntyre, Robin C.; Medeiros, Nelson; et al. (University of Alberta Press, 2016)
Bill 6, the government of Alberta’s contentious farm workers’ safety legislation, sparked public debate as no other legislation has done in recent years. The Enhanced Protection for Farm and Ranch Workers Act provides a right to work safely and a compensation system for those killed or injured at work, similar to other provinces. In nine essays, contributors to Farm Workers in Western Canada place this legislation in context. They look at the origins, work conditions, and precarious lives of farm workers in terms of larger historical forces such as colonialism, land rights, and racism. They also examine how the rights and privileges of farm workers, including seasonal and temporary foreign workers, conflict with those of their employers, and reveal the barriers many face by being excluded from most statutory employment laws, sometimes in violation of the Canadian Charter of Rights and Freedoms. – Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/farmworkersinwes0000unse/mode/2up
Keywords: Agricultural laborers; Canada; Western; Canada; Western. Agricultural laborers; Legal status; laws; etc.; Legal status; laws; etc. Agricultural laborers; Social conditions. Agricultural laws and legislation

Rethinking Canada: The Promise of Women's History - Campbell, Lara; Myers, Tamara; Perry, Adele (Oxford University Press, 2016)
Now in its seventh edition, Rethinking Canada presents compelling essays on the fascinating lives, struggles, and contributions of women in Canadian history. Reflecting an interdisciplinary approach, this comprehensive and engaging resources stresses the diversity of women's history and demonstrates the analytical richness of ongoing research in the field. Featuring insightful chapter introductions that provide scholarly and historical context for each reading, [the book] helps students gain a more nuanced understanding of women's experiences across Canads's history. –Publisher's description
Keywords: Women – Canada – History – Textbooks

Imperial Plots: Women, Land, and the Spadework of British Colonialism on the Canadian Prairies - Carter, Sarah (University of Manitoba Press, 2016)
Sarah Carter's "Imperial Plots: Women, Land, and the Spadework of British Colonialism on the Canadian Prairies" examines the goals, aspirations, and challenges met by women who sought land of their own. Supporters of British women homesteaders argued they would contribute to the "spade-work" of the Empire through their imperial plots, replacing foreign settlers and relieving Britain of its surplus women. Yet far into the twentieth century there was persistent opposition to the idea that women could or should farm: British women were to be exemplars of an idealized white femininity, not toiling in the fields. In Canada, heated debates about women farmers touched on issues of ethnicity, race, gender, class, and nation. Despite legal and cultural obstacles and discrimination, British women did acquire land as homesteaders, farmers, ranchers, and speculators on the Canadian prairies. They participated in the project of dispossessing Indigenous people. Their complicity was, however, ambiguous and restricted because they were excluded from the power and privileges of their male counterparts. Imperial Plots depicts the female farmers and ranchers of the prairies, from the Indigenous women agriculturalists of the Plains, to the land army women of the First World War. –Publisher's description
https://en.wikipedia.org/wiki/Imperial_Plots OCLC: 948339711

Unfree Labour? Struggles of Migrant and Immigrant Workers in Canada - Choudry, Aziz; Smith, Adrian (PM Press, 2016)
Over the past decade, Canada has experienced considerable growth in labour migration. Moreover, temporary labour migration has replaced permanent immigration as the primary means by which people enter Canada. Utilizing the rhetoric of maintaining competitiveness, Canadian employers and the state have ushered in an era of neoliberal migration alongside an agenda of austerity flowing from capitalist crisis. Labour markets have been restructured to render labour more flexible and precarious, and in Canada as in other high-income capitalist labour markets, employers are relying on migrant and immigrant workers as "unfree labour." This book explores labour migration to Canada and how public policies of temporary and guest worker programs function in the global context of work and capitalist restructuring. Contributors are directly engaged with the issues emerging from the influx of temporary foreign workers and Canada's "creeping economic apartheid." –Publisher's description
https://openlibrary.org/books/OL28818494M/Unfree_Labour
Keywords: Canada; Foreign workers; Foreign workers Canada; Foreign workers Canada Social conditions; Foreign workers Government policy; Foreign workers Government policy Canada; Foreign workers Social conditions

Animals, Work, and the Promise of Interspecies Solidarity - Coulter, Kendra (Palgrave Macmillan, 2016)
In this thought-provoking and innovative book, Kendra Coulter examines the diversity of work done with, by, and for animals. Interweaving human-animal studies, labor theories and research, and feminist political economy, Coulter develops a unique analysis of the accomplishments, complexities, problems, and possibilities of multispecies and interspecies labor. She fosters a nuanced, multi-faceted approach to labor that takes human and animal well-being seriously and challenges readers to not only think deeply and differently about animals and work but to reflect on the potential for interspecies solidarity. The result is an engaging, expansive, and path-making text. –Publisher's description
https://www.researchgate.net/publication/306124991_Animals_Work_and_the_Promise_of_Interspecies_Solidarity

Hired Hands: Labour and the Development of Prairie Agriculture, 1880-1930 - Danysk, Cecilia (University of Toronto Press, 2016)
Farm workers were central to the development of Canada's prairie West. From 1878, when the first shipment of prairie grain went to international markets, to 1929, when the Great Depression signalled the end of the wheat boom, the role of hired hands changed dramatically. Prior to World War One, hired hands viewed themselves and were treated in the rural community as equals to their farmer employers. Many were farmers in training, informal apprentices who worked for wages so they could accumulate the capital and experience needed to secure their own free 160-acre parcels of land. In later years, as free lands were taken, hired hands increasingly faced the hkehhood of remaining waged labourers on the farms of others. They became agricultural proletarians. In this first full-length study of labour in Canadian prairie agriculture during the period of settlement and expansion, Cecilia Danysk examines the changing work and the growing rural community of the West through the eyes of the workers themselves. World War One was a catalyst in bringing into focus the conflicting nature of labour-capital relations and the divergent aims of workers and their employers. Yet, attempts at union organization were unsuccessful because most hired hands worked alone and because governments assisted farmers by stifling such attempts. The workers' greatest form of workplace control was to walk off one job and find another. –Publisher's description. Previously published in 1995 by McClelland & Stewart. Contents: Introduction – Labour-Capital Relations in Prairie Agriculture – Part 1. Beginnings, 1870s-1900. Recruiting the Agricultural Labour Force. Part 2. Expansion, 1900-1918. Agricultural Labour as Apprenticeship – Class, Culture, and Community – The Nature of Work –Part 3. Consolidation, 1918-1930. Proletarianization – The Dialectic of Consent and Resistance – Conclusion – Appendix – Notes – Index.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/hiredhandslabour0000dany OCLC: 1013941170

Alien Capital: Asian Racialization and the Logic of Settler Colonial Capitalism - Day, Iyko (Duke University Press, 2016)
In [this book] Iyko Day retheorizes the history and logic of settler colonialism by examining its intersection with capitalism and the racialization of Asian immigrants to Canada and the United States. Day explores how the historical alignment of Asian bodies and labor with capital's abstract and negative dimensions became one of settler colonialism's foundational and defining features. This alignment allowed white settlers to gloss over and expunge their complicity with capitalist exploitation from their collective memory. Day reveals this process through an analysis of a diverse body of Asian North American literature and visual culture, including depictions of Chinese railroad labor in the 1880s, filmic and literary responses to Japanese internment in the 1940s, and more recent examinations of the relations between free trade, national borders, and migrant labor. In highlighting these artists' reworking and exposing of the economic modalities of Asian racialized labor, Day pushes beyond existing approaches to settler colonialism as a Native/settler binary to formulate it as a dynamic triangulation of Native, settler, and alien populations and positionalities. –Publisher's description
OCLC: 910856272
Keywords: Amérique du Nord Relations raciales Aspect économique; Asians North America Public opinion; Asians Public opinion; Asians Race identity North America; Asiatiques Amérique du Nord Opinion publique; Asiatiques Identité ethnique Amérique du Nord; Capitalism Social aspects; Capitalism Social aspects North America History; History; North America; North America Race relations Economic aspects; Race relations Economic aspects; Stereotypes (Social psychology); Stereotypes (Social psychology) North America; Stéréotypes Amérique du Nord

Ginger Goodwin: A Worker's Friend - Ellyn, Laura (Between the Lines, 2016)
With bright, strong imagery, Ginger Goodwin presents the story of labour activist and martyr Albert “Ginger” Goodwin. This accessible and thoughtful graphic history explores Goodwin’s life, work, and death in the mining communities of Cumberland and Trail, British Columbia. Drawing on local history, and exploring the ways the history of labour organizing affects contemporary movements, Ginger Goodwin is a story that needs to be shared. –Publisher's description
OCLC: 910986456

Health and Safety in Canadian Workplaces - Foster, Jason; Barnetson, Bob (Athabasca University Press, 2016)
Workplace injuries happen every day and can profoundly affect workers, their families, and the communities in which they live. This textbook provides workers and students with an introduction to effective injury prevention. It pays particular attention to how issues of precarious employment, gender, and ill-health can be better handled in Canadian occupational health and safety (OHS). Health and Safety in Canadian Workplaces offers an extensive overview of central OHS concepts and practices and provides practical suggestions for health and safety advocacy. It attempts to bring OHS into a twenty-first century context by discussing contemporary workplaces and the health effects of new work processes and structures while recognizing that safety has gendered and racialized dimensions. Foster and Barnetson contend that the practice of occupational health and safety can only be understood if we acknowledge that workers and employers have conflicting interests. Who identifies what workplace hazards should be controlled is therefore a product of the broader political economy of employment and one that should be well understood by those working in the field. – Publisher's description. Contents: Workplace injury in theory and practice – Legislative framework of injury prevention and compensation – Hazard recognition, assessment and control – Physical hazards – Chemical and biological hazards – Psycho-social hazards – Health effects of employment – Training and injury prevention programs – Incident investigation – Disability management and return to work – The practice of health and safety.
OCLC: 951835395
Keywords: Canada; Industrial safety

Canada since 1960: A People's History: A Left Perspective on 50 Years of Politics, Economics and Culture - Gonick, Cy (Lorimer, 2016)
When Winnipeg's Cy Gonick started the magazine Canadian Dimension in 1963 to provide a home for the thinking and analysis of mostly young leftists engaged in Canadian economic, social, cultural, artistic and political issues, he had no grand plan. But Canadian Dimension was welcomed by intellectuals, scholars and students, and it proved enduring. Hundreds of Canada's leading figures of the left have contributed to its pages over the years, writing about every major topic in Canadian public life. This book offers an account of the most important developments in Canadian history from the sixties until today, as seen and interpreted by scholars and writers on the pages of Dimension. Each chapter reviews a major theme, such as Canada's relationship to the U.S., the development of our health care system, the dynamics of Aboriginal-non-Aboriginal relations and the role of Canadian cultural work in shaping Canadian society. Taken together, the book provides a unique and broad perspective on virtually every significant event and development in recent Canadian history. Readers who know the magazine will find this book a compelling summary of how Canada changed in the past five decades, and how the Left saw those changes and challenged them. Readers who discover Canadian Dimension through this book will find a multitude of compelling voices who challenge the dominant neoliberal thinking of mainstream Canadian intellectual life. –Publisher's description.
Keywords: New Left – Canada

Bedside Matters: The Transformation of Canadian Nursing, 1900-1990 - McPherson, Kathryn (University of Toronto Press, 2016)
Nursing embodies the seemingly timeless characteristics of feminine healing, caring, and nurturing, yet this archetypally female vocation also boasts a distinctive and complex history. Bedside Matters traces four generations of Canadian nurses to explore changes in who became nurses, what work they performed, and how they organized to defend their occupational interests. Whether in the apprenticeship method of the early twentieth century or in the present day restructuring of hospital work, the position of nurses within the health-care system has been structured by class, gender, and ethnic and racial relations. Located between the doctors and untrained or subsidiary patient-care attendants, nurses have struggled to define the boundaries of their occupation vis à vis other members of the health-care hierarchy, even as tensions between bedside and administrative nurses created divisions within nursing itself. Focusing on the daily labours of 'ordinary nurses', McPherson argues that the persisting sex-typing of nursing as women's work has meant that gender consistently complicated nursing's easy categorization as either professional or proletariat. Combining archival records and oral histories, the author shows how nurses, in their work, activities, and social and sexual attitudes, sought recognition as skilled workers in the health-care system. –Publisher's description
OCLC: 1013948942

Inégalités, modes d'emploi: l'analyse sociologique des injustices dans le champ de l'emploi au Canada - Moulin, Stéphane (Presses de l'Université de Montréal, 2016)
Les débats sur les inégalités dans l’emploi adoptent habituellement un point de vue économique en se concentrant sur la distribution des revenus plutôt que sur les processus de différenciation sociale. Pourtant, avant d’être un facteur de production, le travail est foncièrement un rapport social, essentiel à l’intégration des individus. La question des inégalités dans l’emploi doit donc être approchée d’un point de vue sociologique. C’est ce que propose cet ouvrage qui, tout en s’inscrivant dans les débats en cours sur la justice sociale, offre une synthèse remarquable des perspectives théoriques, historiques et comparatives sur les inégalités dans les relations d’emploi. Se fondant sur un ensemble de données statistiques récentes, l’auteur décrit les forces qui animent le champ de l’emploi et qui contribuent à définir le statut social au Canada, et dégage ainsi le rôle décisif des politiques publiques dans ce domaine.
https://books.openedition.org/pum/2701?lang=en
Keywords: Canada; Marché du travail; Sociologie industrielle

Three Men: Three Radical Canadian Voices WWI to ca. 1980 - Murphy, Harvey; Knight, Rolf; Smith, John; Arntzen, Arnt (Draegerman, 2016)
The accounts of three men who are presented here were members of the left in Canada between the first decade of the twentieth century until the late 1970s, when their stories were compiled. –Preface
OCLC: 993881723

The Fate of Labour Socialism: The Co-Operative Commonwealth Federation and the Dream of a Working-Class Future - Naylor, James (University of Toronto Press, 2016)
Almost a century before the New Democratic Party rode the first "orange wave," their predecessors imagined a movement that could rally Canadians against economic insecurity, win access to necessary services such as health care, and confront the threat of war. The party they built during the Great Depression, the Co-operative Commonwealth Federation (CCF), permanently transformed the country's politics. Past histories have described the CCF as social democrats guided by middle-class intellectuals, a party which shied away from labour radicalism and communist agitation. James Naylor's assiduous research tells a very different story: a CCF created by working-class activists steeped in Marxist ideology who sought to create a movement that would be both loyal to its socialist principles and appealing to the wider electorate. The Fate of Labour Socialism is a fundamental reexamination of the CCF and Canadian working-class politics in the 1930s, one that will help historians better understand Canada's political, intellectual, and labour history. –Publisher's description.
Available at Internet Archive to readers with print disabilities: https://archive.org/details/fateoflaboursoci0000nayl OCLC: 922452663
Keywords: 20th century. Labor; 20th century. Partis politiques; 20th century. Socialism; 20th century. Working class; Canada; Histoire; History; Political activity; Political parties

Toronto's Poor: A Rebellious History - Palmer, Bryan D.; Héroux, Gaétan (Between the Lines, 2016)
Toronto’s Poor reveals the long and too often forgotten history of poor people’s resistance. It details how the homeless, the unemployed, and the destitute have struggled to survive and secure food and shelter in the wake of the many panics, downturns, recessions, and depressions that punctuate the years from the 1830s to the present. Written by a historian of the working-class and a poor people’s activist, this is a rebellious book that links past and present in an almost two-hundred year story of struggle and resistance. It is about men, women, and children relegated to lives of desperation by an uncaring system, and how they have refused to be defeated. In that refusal, and in winning better conditions for themselves, Toronto’s poor create the possibility of a new kind of society, one ordered not by acquisition and individual advance, but by appreciations of collective rights and responsibilities. –Publisher's description

Working Mothers and the Child Care Dilemma: A History of British Columbia's Social Policy - Pasolli, Lisa (UBC Press, 2016)
Finding affordable, quality child care is a challenge for many Canadian families. In some areas of British Columbia, expectant mothers place their children on daycare waiting lists months before they are born. Yet, despite the demand, recent efforts to achieve a universal child care program have stalled. As Working Mothers and the Child Care Dilemma demonstrates, this is nothing new: child care policy in British Columbia has matured in the shadow of a persistent political uneasiness with working motherhood. Charting the growth of the child care movement in this province, Lisa Pasolli examines the arrival of Vancouver’s first crèche in 1912, the teetering steps forward during the debates of the interwar years, the development of child care policy, the rebellious advancements of second-wave feminists in the 1960s and 1970s, and the maturation of provincial and national child care politics since the mid-70s. In addition to revealing much about historical attitudes toward women’s roles at home and in the workplace, Working Mothers and the Child Care Dilemma celebrates the efforts of mothers and advocates who, for decades, have lobbied for child care as a central part of women’s rights as workers, parents, and citizens.... –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/workingmothersch0000paso OCLC: 942836959
Keywords: 1900-1999; British Columbia; Child care; Child care British Columbia; Child care Government policy; Child care Government policy British Columbia History 20th century; Colombie-Britannique Politique sociale Histoire 20e siècle; Enfants Soins Politique gouvernementale Colombie-Britannique Histoire 20e siècle; History; Maternité Colombie-Britannique Histoire 20e siècle; Motherhood; Motherhood British Columbia History 20th century; Mères au travail Colombie-Britannique; Mères au travail Colombie-Britannique Conditions sociales 20e siècle; Travail et familles Colombie-Britannique; Women Employment; Women Employment British Columbia; Work and family; Work and family British Columbia; Working mothers; Working mothers British Columbia; Working mothers British Columbia Social conditions 20th century; Working mothers Social conditions

Worker Voice: Employee Representation in the Workplace in Australia, Canada, Germany, the UK and the US, 1914-1939 - Patmore, Greg (Liverpool University Press, 2016)
This book informs debates about worker participation in the workplace or worker voice by analysing comparative historical data relating to these ideas during the inter-war period in Australia, Canada, Germany, the UK and the US. The issue is topical because of the contemporary shift to a workplace focus in many countries without a corresponding development of infrastructure at the workplace level, and because of the growing ‘representation gap’ as union membership declines. Some commentators have called for the introduction of works councils to address these issues. Other scholars have gone back and examined the experiences with the non-union Employee Representation Plans (ERPs) in Canada and the US. This book will test these claims through examining and comparing the historical record of previous efforts of five countries during a rich period of experimentation between the Wars. –Publisher's description.
OCLC: 968347966

Social Determinants of Health: Canadian Perspectives - Raphael, Dennis (Canadian Scholars' Press, 2016)
The third edition of Social Determinants of Health focuses on the socio-economic conditions that shape the health of individuals and communities. This edited collection includes contributions from top academics and high-profile experts from across the country. The chapters take a public policy approach that sees the mainsprings of health emerging from the social distribution of resources. The collection as a whole integrates insights from the health sciences, the sociology of health, and the political economy of health. This revised edition has been well updated and includes a greater focus on the political pathways and mechanisms that explain how the social determinants of health come to be distributed amongst the population; early childhood development in Canada in relation to other developed nations; Indigenous health and its determinants; public policy and the social safety net; and the growing network of civil society organizations addressing the inequitable distribution of the social determinants of health. –Publisher's description
Keywords: Public health – Social aspects – Canada

A Future Without Hate or Need: The Promise of the Jewish Left in Canada - Reiter, Ester (Between the Lines, 2016)
Driven from their homes in Russia, Poland, and Romania by pogroms and poverty, many Jews who came to Canada in the wave of immigration after the 1905 Russian revolution were committed radicals. A Future Without Hate or Need brings to life the rich and multi-layered lives of a dissident political community, their shared experiences and community-building cultural projects, as they attempted to weave together their ethnic particularity—their identity as Jews—with their internationalist class politics.–Publisher's description
OCLC: 957507446
Keywords: 1900-1999; Canada; Canada Emigration and immigration History 20th century; Canada Émigration et immigration Histoire 20e siècle; Communism and Judaism; Communism and Judaism Canada History 20th century; Communisme et judaïsme Canada Histoire 20e siècle; History; Jewish socialists Canada; Jews; Jews Canada History; Jews Canada History 20th century; Jews Canada Identity; Jews Canada Politics and government; Jews Canada Social life and customs; Jews Identity; Jews Political activity Canada; Jews Politics and government; Jews Social life and customs; Judaism and politics; Judaism and politics Canada History 20th century; Judaïsme et politique Canada Histoire 20e siècle; Juifs Canada Histoire; Juifs Canada Histoire 20e siècle; Juifs Canada Identité; Juifs Canada Mœurs et coutumes; Juifs Canada Politique et gouvernement; Socialism and Judaism; Socialism and Judaism Canada History 20th century; Socialisme et judaïsme Canada Histoire 20e siècle

Building Global Labor Solidarity in a Time of Accelerating Globalization - Scipes, Kim (Haymarket Books, 2016)
Since the 1980s, the world’s working class has been under continual assault by the forces of neoliberalism and imperialism. In response, new labor movements have emerged across the Global South—from Brazil and South Africa to Indonesia and Pakistan.Building Global Labor Solidarity in a Time of Accelerating Globalization is a call for international solidarity to resist the assaults on labor’s power. This collection of essays by international labor activists and academics examines models of worker solidarity, different forms of labor organizations, and those models’ and organizations’ relationships to social movements and civil society. –Publisher's description.
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/buildinggloballa0000scip/mode/2up

Not Talking Union: An Oral History of North American Mennonites and Labour - Thiessen, Janis (McGill-Queen's University Press, 2016)
This book investigates the labour history of a people who have not been involved in the twentieth-century labour movement in large numbers: North American Mennonites. It explores their historically-constructed attitudes toward organized labour and unions, which it attempts to understand on its own terms. Although Mennonites are typically associated with rural life, they in fact became very involved as workers in specific locations in both traditional Mennonite enclaves in Ohio, Indiana, Ontario, and Manitoba, and those to which they migrated in the twentieth century, such as British Columbia and California. Mennonites in these locales found employment both as field workers for large agri-business operations (for example, the orchards and packing plants of the San Joaquin Valley in California) and as factory hands in manufacturing firms (such as the automotive factories in southern Ontario). The late twentieth century experiences of North American Mennonites in these settings caused them to confront and reassess their attitudes toward unions. A study of these Mennonites–united by transnational ties of ethnic and religious identity yet shaped, at times, in distinct ways by their differing geographic locations, immigration histories and ethnic origins, denominational ties, and class positions–provides insights into how and why the majority of North American Mennonites have rejected labour unions in the late twentieth and early twenty-first centuries. The oral histories of the 113 Mennonites interviewed provide insight into why many working North Americans are not union supporters, and how people in general negotiate tensions between their commitments to faith and conscience and the demands of their employment. An important aim of the book is to bring labour historians and historians of religion into conversation. –Publisher's description
OCLC: 952565535

A Town Called Asbestos: Environmental Contamination, Health, and Resilience in a Resource Community - Van Horssen, Jessica (UBC Press, 2016)
For decades, manufacturers from around the world relied on asbestos from the town of Asbestos, Quebec, to produce fire-retardant products. Then, over time, people learned about the mineral's devastating effects on human health. Dependent on this deadly industry for their community's survival, the residents of Asbestos developed a unique, place-based understanding of their local environment; the risks they faced living next to the giant opencast mine; and their place within the global resource trade. This book unearths the local/global tensions that defined Asbestos's proud and painful history to reveal the challenges similar resource communities have faced–and continue to face today. – Publisher's description. Contents: Foreword: the long dying / Graeme Wynn – Introduction: introducing Asbestos – Creation stories: Asbestos before 1918 – Land with a future, not a past, 1918-49 – Negotiating risk, 1918-49 – Essential characteristics, 1918-49 – Bodies collide: the strike of 1949 – "Une ville qui se deplace," 1949-83 – Useful tools, 1949-83 – Altered authority, 1949-83 – Conclusion: surviving collapse: Asbestos post-1983.
OCLC: 919340340
Keywords: Asbestos mines and mining; Asbestos. Amiante; Asbestos. Asbestos industry; Asbestos. Asbestos mines and mining; Asbestos. Asbestos. Environmental Exposure; Aspect de l'environnement; Aspect politique; Aspect sanitaire; Environmental aspects; Health aspects; Industrie; Mines et extraction; Political aspects; Qubec (Province); economics. Cities; economics. History; 20th Century; history. Environmental Illness; psychology. Denial (Psychology) Mining

Building the Power: The Labourers' Union in British Columbia - Warrior, M. C. (Construction and Specialized Workers' Union, LiUNA Local 1611, 2016)
“Building The Power” is a fascinating look into the history of LiUNA Local 1611, documenting the dramatic events and accomplishments of its members since 1937, written by Local 1611’s Strategic Researcher and labour activist Mark Warrior. In 1953, Stacey Warner, while organizing pipeline workers, was threatened with a shotgun by a company thug hired for the sole purpose of intimidation. The police did not take notice. In 1981, the Labour Relations Board ignored the fact that the employer offered union member a $1,000 bribe to change his vote—right at the Labour Relations Board office—when LiUNA Local 1070 was attempting to certify his bargaining unit. Ignoring naked violence had been replaced by ignoring blatant lawbreaking. But the result was not the same. Warner succeeded in organizing the workers. These are examples of the conflict and often dangerous scenarios those in the Labour Movement have faced in their effort to secure workers’ right and fair working wages and safe working conditions. –Website description
OCLC: 1083230488
Keywords: Laborers' International Union of North America; Laborers' International Union of North America. Local 1611

North to Bondage: Loyalist Slavery in the Maritimes - Whitfield, Harvey Amani (UBC Press, 2016)
Many Canadians believe their nation fell on the right side of history in harbouring escaped slaves from the United States. In fact, in the wake of the American Revolution, many Loyalist families brought slaves with them when they settled in the Maritime colonies of British North America. Once there, slaves used their traditions of survival, resistance, and kinship networks to negotiate their new reality. Harvey Amani Whitfield’s book, the first on slavery in the Maritimes, is a startling corrective to the enduring and triumphant narrative of Canada as a land of freedom at the end of the Underground Railroad. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/northtobondagelo0000whit